The Impact of Workplace Well-Being and Ethical Leadership on Employee Performance - La Ode Obi; Lisa Gresti Sella Damanik; Mutiasari; Aulia nurlaili kusuma wardani; Dipa Teruna Awaludin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the relationship between workplace well-being and ethical leadership in influencing employee performance at PT Sinar Glorindo Dinamika Semarang. The population of this study consisted of 123 employees at PT Sinar Glorindo Dinamika. The sampling method used was a census. This study employed a quantitative approach, with multiple linear regression analysis as the analytical technique. The results indicate that workplace well-being and ethical leadership, both partially and simultaneously, have a positive and significant influence on employee performance. These findings suggest that employee well-being serves as an important mechanism through which relational and ethical organizational resources are translated into improved performance outcomes. The implications of this study provide important managerial insights, suggesting that organizations should prioritize developing collaboration and strengthening ethical leadership practices to create a supportive work environment. Enhancing workplace well-being can serve as a strategic approach to improving employee performance. Furthermore, this study contributes to the literature by integrating ethics and well-being into a comprehensive performance model.